A post-synthetic approach triggers selective and reversible sulphur dioxide adsorption on a metal–organic framework. Issue 65 (27th July 2018) - Mon, Marta; Tiburcio, Estefanía; Ferrando-Soria, Jesús; Gil San Millán, Rodrigo; Navarro, Jorge A. R.; Armentano, Donatella; Pardo, Emilio
Abstract : We report the application of a post-synthetic solid-state cation-exchange process to afford a novel 3D MOF with hydrated barium cations hosted at pores able to trigger selective and reversible SO2 adsorption. Abstract : We report the application of a post-synthetic solid-state cation-exchange process to afford a novel 3D MOF with hydrated barium cations hosted at pores able to trigger selective and reversible SO2 adsorption. Computational modelling supports the full reversibility of the adsorption process on the basis of weak supramolecular interactions between SO2 and coordinated water molecules.